2021
DOI: 10.3390/asi4010010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fruit and Vegetable Residues Suitable for Renewable Energy Production: GIS-Based Model for Developing New Frontiers within the Context of Circular Economy

Abstract: Due to the necessity of developing renewable energy sources, the anaerobic digestion for producing biomethane has developed significantly in the last years, since it allows to both reduce disposal treatment and produce green energy. In this field, fruit and vegetable wastes have been recently put forward, since they could represent a suitable resource for producing biomethane as a new frontier within the context of a circular economy. This study aims at filling the gap in the knowledge of the production, quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Today, these findings are crucial for minimizing environmental impacts derived from the logistic-supplying phase, so it is important to plan the suitable locations for new plants (both considered types) in a circular and green economy perspective. Some research studies were carried out by combining GIS tool and statistical database, by taking into account different sources of biomass, but with the same objective of reducing environmental impacts related to logistic supply phase, with the key criterion of minimizing transportation cost [5,7,42,43]. In line with the results reported here, all of these studies demonstrated that new bioenergy plants must be located as near as possible to the biomasses production sites.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Today, these findings are crucial for minimizing environmental impacts derived from the logistic-supplying phase, so it is important to plan the suitable locations for new plants (both considered types) in a circular and green economy perspective. Some research studies were carried out by combining GIS tool and statistical database, by taking into account different sources of biomass, but with the same objective of reducing environmental impacts related to logistic supply phase, with the key criterion of minimizing transportation cost [5,7,42,43]. In line with the results reported here, all of these studies demonstrated that new bioenergy plants must be located as near as possible to the biomasses production sites.…”
Section: Resultssupporting
confidence: 67%
“…With this increasing population, a significant amount of fuel may be in demand to aid the energy requirements in the coming years [2]. The renewable energy sources for producing electricity and heat could reduce the negative impact of fossil fuels on GHG released into the atmosphere [3][4][5] by playing a key role in the current CO2 mitigation policies. Among the suitable renewable energy sources that the past few decades have been developed, biomasses are one of the most important renewable energy sources [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are several manuscripts available in the literature reporting the relevant role that anaerobic digestion should exert in a circular economy model, considering the capability of this process for producing energy from organics, manures, and a great diversity of agronomic wastes [10][11][12][13]. Table 1 lists the products associated with the role of anaerobic digestion in the circular economy based on scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…In Sicily, greenhouses horticultural cultivations are mainly concentrated in the province of Ragusa, in the southern coastal area, where more than 56% of the Sicilian greenhouse surface is located [41].…”
Section: Case Studymentioning
confidence: 99%
“…In this regard, anaerobic digestion (AD) of agricultural by-products (e.g., animal slurry, food waste, food processing residues) has been recognized by several studies [34][35][36] as a suitable and effective solution to produce renewable energy by means of a cogeneration system (electricity (EE) and thermal energy (TE)) [37][38][39]. In detail, the exploitation of biomass for producing biogas by anaerobic digestion (AD) shows high potential to meet the challenges of sustainable and green energy [40,41].…”
Section: Introductionmentioning
confidence: 99%